2019
DOI: 10.3390/molecules24040670
|View full text |Cite
|
Sign up to set email alerts
|

Greek Graviera Cheese Assessment through Elemental Metabolomics—Implications for Authentication, Safety and Nutrition

Abstract: This study presents the comprehensive elemental profile of Greek Graviera (Gruyère) cheeses. In total, 105 samples from nine different geographic regions produced from sheep, goat and cow milk and their mixtures were assessed. Elemental signatures of 61 elements were investigated for determination of geographic origin and milk type. Regional and milk type classification through Linear Discriminant Analysis was successful for almost all cases, while a less optimistic cross validation exercise presented lower cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Results of the present study regarding mineral content are in general agreement with those of Gonzalez-Martin et al [ 29 ] who determined the mineral content of cow, sheep and goat milk from Zamora, Spain. Danezis et al [ 25 ] reported the signature of 61 elements in Greek graviera cheeses including all sixteen rare earth elements and all seven precious metals which were used to differentiate cheese geographical origin. Likewise, Vatavali et al [ 26 ] determined among other analytical parameters, a similar profile of minerals for graviera cheeses from six different geographical origins in Greece.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the present study regarding mineral content are in general agreement with those of Gonzalez-Martin et al [ 29 ] who determined the mineral content of cow, sheep and goat milk from Zamora, Spain. Danezis et al [ 25 ] reported the signature of 61 elements in Greek graviera cheeses including all sixteen rare earth elements and all seven precious metals which were used to differentiate cheese geographical origin. Likewise, Vatavali et al [ 26 ] determined among other analytical parameters, a similar profile of minerals for graviera cheeses from six different geographical origins in Greece.…”
Section: Resultsmentioning
confidence: 99%
“…However, the method was not always able to discriminate between PDO and non-PDO buffalo mozzarella originating from the same production area. Recently, Danezis et al [25] determined the elemental profile of 105 graviera cheeses from nine different geographic regions in Greece in an effort to differentiate the cheeses based on geographical origin and milk type. Cheeses were produced from sheep, goat, and cow milk, as well as their mixtures.…”
Section: Discrimination Of Graviera Cheeses Based On Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cheese geographical origin authentication, ICP-MS is the preferred choice since it is a rapid, multi-element analysis able to quantify trace (ppm–ppb) or ultra-trace (ppb–ppq) elemental concentrations [ 49 ]. As elemental composition is mainly affected by geological and pedological traits, multiple factors can affect the element content in cheese, such as animal breed, feed vegetation, drinking water, and mineral supplementation [ 49 , 50 ]. Possible effects of cheese-making on cheese elements could derive from the clotting agent, curd acidification, manufacturing equipment, curd washing, and salt washing/brining [ 34 , 51 ].…”
Section: Chemical and Physical Methods For Cheese Origin Authenticationmentioning
confidence: 99%
“…Elemental Metabolomics based on Elemental Mass spectrometry [ 82 ] has been applied for food authentication [ 83 ], as well as determination of geographic, genetic and processing origin. Applications concern the geographical and botanical type of honey [ 84 ], authentication of Greek Protected Designation of Origin cheeses [ 85 ], modulation of egg metallome with flavonoids [ 86 ], authentication, safety and nutrition of Graviera Cheese [ 87 ], and determination of meat production methods (wild vs. farmed) [ 88 ]. Elemental metabolomics applied to PDO “Fava Santorinis” [ 89 ] revealed that rare earth elements’ minimal harvest year variation facilitates robust geographical origin discrimination, while data fusion with trace elements discriminates “Fava Santorinis” from other yellow split peas [ 90 ].…”
Section: Foodomicsgr_ri Plan and Strategymentioning
confidence: 99%